A HISTORICAL CYCLE OF GUSTAVE FLAUBERT'S EARLY PROSE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the early, unpublished works during Flaubert's lifetime, which are evidence of the formation of creative individuality, an organic part of Flaubert's artistic world and a significant fact of the history of literature. The formation of Flaubert's creative personality unfolds in line with Western European literary, aesthetic and philosophical traditions. Flaubert is interested not only in the feelings of the individual, as it was before, but also in the psychology of the mass. He is interested in the contrasting changes in the mood of the crowd: the stormy joy of the citizens of Rouen greeting the king, the fury with which the same people storm the town hall to save Richard, and again the delight at the news that the heir to the duchy of Normandy is alive. The "Norman Chronicle" became the boundary between "student" essays and works that went beyond school exercises, created at the end of 1836: "The Secret of Philip the Cautious" and "The Plague in Florence". Flaubert himself calls them not transcriptions, but historical short stories. The basis of his worldview were the works of ancient authors, the ideas of writers and philosophers of the Renaissance, the XVII century, the Enlightenment and Romanticism.